The year of the book - Cheng, Andrea; Halpin, Abigail (Boston : Houghton Mifflin, 2012)
Follows a young Chinese American girl, as she navigates relationships with family, friends, and her fourth-grade classroom, and finds a true best friend.
Grades 3-5.
A Junior Library Guild selection, 2012.
Keywords: Chinese Americans -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Chinese Americans -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction